Rastros e vozes de Sylvia Plath: reminiscências e memória. - Carvalho, Taísa (2013)
The purpose of this paper is to analyze, in a comparative way, the theme of melancholy, suicide, and death in eight Ariel poems the work of Sylvia Plath - "Lady Lazarus", "Daddy", "The moon and the yew tree "," Death & Co ", "Ariel," Tulips "," The detective "and" Purdah "- in five poems from other works of the same writer -" Pursuit "," the tree of life "," Mirror "," Edge "and" Words "- in four paintings entitled Vita e Morte , Allegoria la vita unama , La morte del peccatore and Melancolia I and the movie Sylvia , passion beyond words by Christine Jeffs. Based on the established thematic intertextuality between artistic forms - film, painting and poem - which constitute the corpus of this research and the conception of poetry as a place of culture, studies the poetry of Sylvia Plath, which is constructed by the plots of the imaginary, process and reminiscent of forgetfulness, so that art and suffering may converge and the shadow of suicide author protrudes over the text. It is, above all, a poetic which refers to the human condition of transience and permanence: the permanence of writing and transience of life. Therefore, this study is based mainly on the theoretical principles of Paz (1982, 1991 and 1993), Gagnebin (2005, 2006, 2009), Schopenhauer (2001), Yates (2007), Almeida (1999), Weinrich (2001), Bosi (2000), Adorno (1975), Benjamin (2000), Seligmann-Silva (2010) and Chevalier (2003).